Symptoms of Anxiety and Depression in Young Athletes Using the Hospital Anxiety and Depression Scale - Weber, Stephanie; Puta, Christian; Lesinski, Melanie; Gabriel, Brunhild; Steidten, Thomas; Bär, Karl-Jürgen; Herbsleb, Marco; Granacher, Urs; Gabriel, Holger H. W. (Frontiers in Physiology, 2018)
Elite young athletes have to cope with multiple psychological demands such as training volume, mental and physical fatigue, spatial separation of family and friends or time management problems may lead to reduced mental and physical recovery. While normative data regarding symptoms of anxiety and depression for the general population is available (Hinz and Brähler, 2011), hardly any information exists for adolescents in general and young athletes in particular. Therefore, the aim of this study was to assess overall symptoms of anxiety and depression in young athletes as well as possible sex differences. The survey was carried out within the scope of the study „Resistance Training in Young Athletes“ (KINGS-Study). Between August 2015 and September 2016, 326 young athletes aged (mean±SD) 14.3±1.6 years completed the Hospital Anxiety and Depression Scale (HAD Scale). Regarding the analysis of age on the anxiety and depression subscales, age groups were classified as follows: late childhood (12-14 years) and late adolescence (15-18 years). The participating young athletes were recruited from Olympic weight lifting, handball, judo, track and field athletics, boxing, soccer, gymnastics, ice speed skating, volleyball, and rowing. Anxiety and depression scores were (mean±SD) 4.3±3.0 and 2.8±2.9, respectively. In the subscale anxiety, 22 cases (6.7%) showed subclinical scores and 11 cases (3.4%) showed clinical relevant score values. When analyzing the depression subscale, 31 cases (9.5%) showed subclinical score values and 12 cases (3.7%) showed clinically important values. No significant differences were found between male and female athletes (p≥0.05). No statistically significant differences in the HADS scores were found between male athletes of late childhood and late adolescents (p≥0.05). To the best of our knowledge, this is the first report describing questionnaire based indicators of symptoms of anxiety and depression in young athletes. Our data implies the need for sports medical as well as sports psychiatric support for young athletes. In addition, our results demonstrated that the chronological classification concerning age did not influence HAD Scale outcomes. Future research should focus on sports medical and sports psychiatric interventional approaches with the goal to prevent anxiety and depression as well as teaching coping strategies to young athletes.